Guidelines for food systems issues prioritization and actor and action mapping at sub-national levels in Vietnam - Hanh Tho, Pham Thi; The, Tran Van; Huynh Thi, Tuyen Thanh; Nguyen, Quoc Minh; Even, Brice; Pham Thi, Huong Mai; Viet Anh, Bui Thi; Anh, Dao The (2025)
The guidelines aim to assist provincial and local actors - including government officials, sectoral agencies, and other stakeholders, including the private sector and community organizations - in conducting structured food systems issue prioritization and actor–action mapping. These tools enable stakeholders to identify urgent food system challenges, clarify roles and responsibilities, and coordinate targeted actions. Together, these steps strengthen planning processes, improve alignment across sectors, and contribute to the effective implementation of the NAP-FST at the local level. The guidelines are based on the experiences of NAP-FST implementation at sub-national levels in Dong Thap and Son La provinces between August and December 2024. The tool is designed to be flexible and customizable, allowing provinces to tailor their approaches to specific contexts and stakeholder dynamics.